Multi-wavelength Praseodymium fiber laser using stimulated Brillouin scattering - Ahmad, Harith; Aidit, Siti Nabila; Tiu, Zian Cheak (Elsevier, 2018)
A multi-wavelength Brillouin Praseodymium fiber laser (MWBPFL) operating at 1300 nm region is demonstrated based on the hybrid scheme by utilizing Brillouin gain medium and Praseodymium-doped fluoride fiber as linear gain medium. A 15 µm air gap is incorporated into the cavity to allow the switching of Brillouin frequency spacing from double to single spacing. Under the Brillouin pump of 8 dBm and the 1020 nm pump power of 567.2 mW, 36 Stokes lines with a wavelength spacing of 0.16 nm and 24 Stokes lines with a wavelength spacing of 0.08 nm are achieved. The wavelength tunability of 8 nm is realized for both MWBPFLs by shifting the Brillouin pump wavelength. The MWBPFLs exhibit an excellent stability in the number of generated Stokes and power level over one-hour period.